Peningkatan Kenyamanan Ibu Hamil Trimester III dengan Senam Hamil Berbasis Keluarga - Aswati, Aswati; Erpiana, Dina (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
quality of comfort in pregnant women is very important for the health of the mother and fetus. The cause of the disorder of comfort of pregnant women because, his large stomach, causing the mother to get tired quickly, because caused by the posture that has changed, pregnant women also experience frequent awakening at night to urinate. To overcome this, pregnant gymnastics is done to increase the comfort of pregnant women. Purpose: This study is to describe family nursing care with Efforts to Improve Comfort of Pregnant Women Trimester III. Method: This research is descriptive of analytics with a case study approach. Data is obtained from interviews and observations. Subject of a case study of 1 patient, the time starts in June 2019. Results: After doing Pregnancy exercise for one week pregnant women experience an increased sense of comfort in themselves like the mother feels more comfortable, the patient can rest more, the mother does not wake up at night, the patient feels fresher and improved. Thus there is the influence of Pregnancy exercise on the comfort of pregnant women in the third trimester, it can be concluded that Pregnancy exercise activities can be one of the efforts that can be done to increase the comfort of pregnant women in the third trimester.Keyword: Pregnant